Plan estratégico y logístico, para la implementación de una nueva ruta de servicio de transporte intermunicipal de la empresa Citracom Ltda en el municipio de Combita Boyacá. - Piratova Tocarruncho, Jonathan Stiven; Suárez Roberto, Yurani Caterin (Universidad Antonio Nariño, 2023)
Based on the importance that companies have to have a good operation in the logistics and strategic areas in terms of inter-municipal transport service, two models are proposed within the company Citracom ltda